Analysis of Intelligence Quotient On the Interest In Learning Using Students' Mathematical Communication - Diding Diding Yadi; Anggita Maharani (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2023)
This research aims to determine a significant relationship between mathematical logical intelligence and students' interest in learning mathematics at SMK Manbaul Ulum Cirebon. This research method uses ex post facto which examines causal relationships that are not manipulated or treated (designed and implemented) by researchers. Data collection techniques use interviews and tests. After the data in the study is collected, data analysis is then carried out. In analyzing this used quantitative descriptive statistical analysis methods. The results of this study show that mathematical communication has a positive and significant influence on students' intelligence intelligence and interest in learning.